Normative values and integrated score of functional fitness among Chinese community-dwelling older adults in Suzhou - Xu, Jing; Chen, Ya; Li, Jiaojiao; Zhang, Hui; Shi, Minhao; Meng, Hongyan; Wang, Li (Frontiers in Physiology, 2022)
Objectives: This study was performed to establish the normative values and integrated score of the functional fitness on the basis of the senior fitness test (SFT) among Chinese community-dwelling older adults in Suzhou. Methods: In this cross-sectional descriptive study, 1,122 community-dwelling older adults aged 60 years old and above were recruited at Suzhou, China, by using a multistage stratified sampling method and accepted the SFT measurements. Sex- and age-specific normative values of each index of the SFT were established by using the percentile method. The SFT integrated score was established using factor analysis according to the data of 70% of the participants (construction group) and verified using the error rate from the data of the remaining 30% of the participants (verification group). Results: Normative-referenced percentile values at the 5th, 10th, 25th, 35th, 50th, 65th, 75th, 90th, and 95th percentiles for each index of SFT were established for the men and women among the different age groups. Five indices of the SFT, namely, 2-min step test, 30-s arm curl, 30-s chair stand, chair sit-and-reach, and 8-ft up-and-go (TUGT), gradually declined with age in both sexes (p < .05). The SFT integrated score was calculated as follows: F = 3.8 × 2-min step test + 3.8 × 30-s arm curl + 3.8 × 30-s chair stand + 2.2 × back starch + 2.6 × chair sit-and-reach + 4 × TUGT − .04 × BMI. The formula was verified using the error rate. The error rates of the verification group compared with the construction group in each grade score of SFT were lower than 5%. Conclusion: Based on the data from the community-dwelling older adults in Suzhou, China, the functional fitness normative values for each index of the SFT and the integrated score of SFT were established. The SFT integrated score formula was verified to be reasonable and effective.